Atlas of anesthesia - Reves, J. G. (Current Medicine, 1999)
The fully updated and revised 3rd edition of this one-of-a-kind, full-color atlas helps you perform nerve blocks accurately and successfully in all regions of the body. Step-by-step illustrations demonstrate each technique in a simple, easy-to-follow manner. An emphasis on cross-sectional anatomy, illustrations of gross and surface anatomy, and CT and MRI scans help you develop a three-dimensional concept of anatomy essential to successful regional anesthesia administration.